TNF-α Deficiency Prevents Renal Inflammation and Oxidative Stress in Obese Mice - Huaiguo Wang; Jian Li; Zhibo Gai; Gerd A. Kullak-Ublick; Zewei Liu (Karger Publishers, 2017)
Background/Aims: Obese patients and experimental animals exhibit high levels of inflammatory cytokines, such as tumor necrosis factor (TNF)-α. However, the role of TNF-α in the pathophysiologic process in obesity induced kidney damage is still unknown. Methods: We used TNF-α deficient mice and wild-type (WT) C57/BJ6 mice controls to study the effect of TNF-α on inflammation and oxidative stress in kidney by the model of high-fat diet (HFD) and primary isolated mouse renal proximal tubule cells treated with a mixture of free fatty acids (FFA). Results: Compared with the chow diet group, HFD-fed WT mice had higher urinary albumin and increased levels of renal fibrosis, glomerulosclerosis, inflammation, oxidative stress and apoptosis in the kidney. These changes were co-related with increased expression of TNF-α in the kidney and were attenuated by TNF-α deficiency. In vitro, accumulation of intracellular lipids induced TNF-α expression and oxidative stress in FFA treated primary proximal tubule cells. However, TNF-α inhibition with siRNA or TNF-α deficiency decreased the lipid induced oxidative stress in these cells. Conclusion: These findings suggest that TNF-α plays an important role in the HFD induced kidney damage, and targeting TNF-α and/or its receptors could be a promising therapeutic regimen for progressive nephropathy.